Aircraft skin inspections: towards a new model for dent evaluation - Lafiosca, Pasquale; Fan, Ip-Shing; Avdelidis, Nicolas Peter (British Institute of Non-destructive Testing, 2023)
The aircraft maintenance, repair and overhaul (MRO) industry is gradually switching to 3D scanning for dent inspection. High-accuracy devices allow for quick and repeatable measurements, which translate into efficient reporting and more objective damage evaluations. However, the potential of 3D scanners is far from being exploited. This is due to the traditional way in which the structural repair manual (SRM) deals with dents, that is, considering length, width and depth as the only relevant measures. Being equivalent to describing a dent similarly to a 'box', the current approach discards any information about the actual shape. This leads to a high degree of ambiguity, with very different shapes (and corresponding fatigue life) being classified as the same, and nullifies the effort of acquiring such a great amount of information from high-accuracy 3D scanners. In this paper, a seven-parameter model is proposed to describe the actual dent shape, thus enabling the exploitation of the high-fidelity data produced by 3D scanners. The compact set of values can then be compared against historical data and structural evaluations based on the same model. The proposed approach has been evaluated in both simulations and point cloud data generated by 8tree's dentCHECK tool, suggesting an increased capability in the evaluation of damage, enabling more targeted interventions and, ultimately, saving costs.
Keywords: 3D scanning; Aircraft inspections; Dents; Maintenance; Point clouds